Education kit for autism / Zakhir Zainon - Zainon, Zakhir (Universiti Teknologi MARA, Kedah, 2018)
A family with family members with autism spectrum disorder (ASDI faces many challenges. which affect not only children with ASD and their development but also family function and quality of life. Autism is a developmental disorder that negatively impacts the ability for communication and interaction. A special needs child is a beautiful gift to display God's unfailing love, yet such children also present with unique and highly complex challenges. Autism is very complex, often baffling developmental disability. As an uncle of an 8-year-old boy with Autism Spectrum Disorder (ASD), I know the joy-filled life full of blessings, and the life of heart-wrenching lonely hours of worry and anguish. It is the hours of deep despair and of great joy that inspire me to designed the product that can solving education problems for a child with ASD. To endorses the UNESCO declaration of 'Education for All' and the 'No Child Left Behind' policy for the purpose of sustainable development. My goal is to provide new innovation product to help autism kid to get knowledge.